(3NhGU CSeGA GdLdLhJjIs
(3ChdgG (B:s
(3gPG cJGH ai HjGf NhGU ai GdHjJ GdChd jMUd dbGQFgG GdegGHI s
(3BNQgG (B:s
(3hgPG BNQ eG GfJgi dfG hEdjfG ai TQM GdbUjOI GdeHGQcI GdYXjeI GdeajOI hGddg CYde s
(3GdLdLhJjI (B: (3bUjOI ai (B22 (3HjJkG ai CSeGA Gddg GdMSfis
(3HgG fXGe GdJYbjHIs
(3cJHJ CQbGe GdCHjGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds